ANALISIS STRATEGI MANAJEMEN DALAM MEMPERTAHANKAN BADAN USAHA MILIK DESA (BUMDES) MANDIRI BERSAMA DESA MARINDAL I KECAMATAN PATUMBAK KABUPATEN DELI SERDANG SUMATERA UTARA DI ERA COVID-19 DARI TAHUN 2017-2022 - Daniel Christian Ambarita; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The purpose of this study is to find out how important the goal of forming a management strategy is in maintaining Village-Owned Enterprises (BUMDes) in the Covid-19 era in Marindal I Village, Patumbak District, Deli Serdang Regency which focuses on how Marindal I Village maximizes the potential of its village so that the Owned Enterprise Marindal I Village (BUMDes) can still survive in the Covid-19 era. The research method used in this study used qualitative research with a descriptive research type, namely to describe and explain the important role of the purpose of forming a Management Strategy in maintaining Village-Owned Enterprises (BUMDes) in Marindal I Village, Patumbak District, Deli Serdang Regency. The results of the study show that the management strategy for BUMDes Mandiri Bersama Desa Marindal I has not been fully implemented. This is what has caused BUMDes Mandiri Bersama to be late in anticipating changes in circumstances and conditions that require Marindal I Village to change the type of business in a bit of a hurry to be able to return to earn Village Original Income (PAD) in the Covid-19 era. Keywords : Analysis, Role, Management Strategy, BUMDes, Endure